Recent progress on biological control of Fusarium wilt in vegetable crops - Feng Xiong; Mingfeng Guo; Yawen Liu; Xiaochen Liu; Jiahui Fu; JunZhu Gao; Man Yang; Rui Ma; Tingyu Zhang; Xuesheng Liu; Yu Jin; Juanjuan Qu (Crop Protection, 2026)

CFD-DEM simulations on the flow mechanisms and pressure transfer characteristics of foam-conditioned sands in a shield chamber - Daobing Zhang; Zheng Wang; Junqiu Ma; Qiujing Pan; Hao Xiong; Mingfeng Lei (Computers and Geotechnics, 2026)

Capsular polysaccharides of the human gut microbiota: Structural diversity, functional plasticity, and roles in host–microbe mutualism - Ziyi Fang; Mingfeng Ma; Guangli Yu; Qingsen Shang (Carbohydrate Polymers, 2026)

Impacts of extreme drought events on forest ecosystem resilience in mainland Southeast Asia - Lusha Ma; Kun Yang; Zongqi Peng; Run Sun; Mingfeng Zhang; Danni Su; Jingcong Ma; Yanhui Zhu; Xianchun Pan (Science Bulletin, 2026)

Corrigendum to ‘Study on nutrient release characteristics of infiltration biochar fertilizer coated by cross-linked chitosan’ [J. Environ. Chem. Eng. 13 (6) (2025) 120190] - Pinghui Wei; Xinyuan Fu; Mingfeng Wang; Weiwei Liu; Qingfa Zhang; Bin Li; Zhong Ma (Journal of Environmental Chemical Engineering, 2026)

Adaptive graph learning with dynamic neural ODE for feeding intensity analysis of pearl gentian grouper in a recirculating aquaculture system - Hongpo Wang; Zeshuang Ma; Hong Zhou; Yunchen Tian; Haohui Liu; Zhanshuo Sun; Lei Jia; Jincheng Hu; Mingfeng Hu (Aquacultural Engineering, 2026)

Intercropping enhances soil organic carbon accumulation by modulating microbial interactions in saline-alkali soils - Lijun Zhang; Guixiang Zhou; Jiabao Zhang; Lin Chen; Congzhi Zhang; Donghao Ma; Hui Zhang; Jian Feng; Mingfeng Liu (Applied Soil Ecology, 2026)

Evaluation of novel probiotic Bacillus candidates from the midgut of gibel carp (Carassius auratus gibelio): effects on fish growth, immunity, and resistance to CyHV-2 infection - Mingming Zhang; Ni Ma; Yaqin Yang; Mingfeng Zhu; Hu Zhang; Zhigang Zhao; Jialin Zhang; Mingzhu Pan; Zhitao Qi; Guo Qiao (Aquaculture International, 2026)

An automated and intelligent monitoring system for shield tunneling muck evaluation integrating multimodal data - Zeyu Yue; Linchong Huang; Yuexiang Lin; Yu Liang; Mingfeng Lei; Jianjun Ma (Journal of Cleaner Production, 2026)

Molten Li/Na/K ternary carbonate salt pyrolysis of biomass: A facile approach for co-production of porous biochar, CO-enriched syngas, and high-selectivity bio-oil - Jiazhen Tang; Tianyu Lu; Xing Xie; Dan Lin; Dongjing Liu; Qingfa Zhang; Mingfeng Wang; Weiwei Liu; Zhong Ma; Haiping Yang; Shihong Zhang; Bin Li (Journal of Cleaner Production, 2026)

Study on nitrogen and phosphorus adsorption from biogas slurry by biochars derived from different feedstocks - Jingjing Luo; Wenyu Jiang; Huan Ma; Mingfeng Wang; Qingfa Zhang; Bin Li; Weiwei Liu (Environment, Development and Sustainability, 2025)

Study on nutrient release characteristics of infiltration biochar fertilizer coated by cross-linked chitosan - Pinghui Wei; Xinyuan Fu; Mingfeng Wang; Weiwei Liu; Qingfa Zhang; Bin Li; Zhong Ma (Journal of Environmental Chemical Engineering, 2025)

Isolation and Identification of Metanophrys sinensis from Shrimps (Litopenaeus vannamei) and Screening of Chinese Herbal Medicines for Its Control - Mingfeng Ge; Yifan Xu; Juan Feng; Zheng Liang; Hao Cui; Xinxin Jiang; Jianping Wang; Shengwei Xu; Rongrong Ma (Fishes, 2025)
The parasitic disease scuticociliatosis poses significant economic losses to shrimp culture. In this study, an unidentified species of ciliates was discovered in Litopenaeus vannamei. Morphological and molecular analyses were conducted to identify the parasite species, while a reinfection experiment was performed to assess its virulence towards L. vannamei. Simultaneously, Chinese herbal medicine was assessed for potential prevention and control of this pathogen. The results revealed that the SSU rDNA (93.87%), LSU rDNA (98.20%), and ITS1-5.8S-ITS2 rDNA (87.10%) genes exhibited high homology with Metanophrys sinensis, suggesting its classification within the genus Metanophry sp. The reinfection experiment demonstrated median lethal dosages of 6638 individuals/mL at 24 h and 4658 individuals/mL at 48 h for this ciliate on the host L.vannamei. In terms of drug control, we conducted a screening of 23 Chinese herbal extracts through in vivo injection trials and observed that Mume fructus extract exhibits potent biocidal activity. Specifically, the M. fructus extract solution with a final concentration of 5 mg/mL (0.5% v/v) eliminated all ciliates within 3 h. In conclusion, this study identified the ciliate parasite as Metanophrys sinensis and demonstrated its virulence to Litopenaeus vannamei. Mume fructus extract was found to effectively control the parasite, offering potential for managing scuticociliatosis in shrimp culture.

Underlying mechanism of sucrose esters on myofibrillar protein O/W emulsion gel behaviour under different ionic strengths: Focus on emulsion characterisation, protein structural changes and molecular interactions - Xiang Li; Bo Wang; Wenwen Hou; Jie Tang; Hongbin Lin; Junqiang Lian; Qian Liu; Mingfeng Xu; Yuan Ma; Dong Yu; Dong Zhang; Jiaxin Chen (Food Chemistry, 2025)

Synergistic effects of PGPR and organic fertilizer on soil fertility, enzyme activities, and microbial community composition in saline-alkali rice systems - Mingfeng Guo; Junzhu Gao; Man Yang; Yawen Liu; Jiahui Fu; Rui Ma; Feng Xiong; Tingyu Zhang; Xuesheng Liu; Yu Jin; Juanjuan Qu (Applied Soil Ecology, 2025)

Restoration of secondary forest in the Greater Mekong Subregion struggles to offset primary forest carbon losses - Zongqi Peng; Yanhui Zhu; Kun Yang; Yi Luo; Xixi Lu; Jiasheng Wang; Yang Zhang; Danni Su; Run Sun; Mingfeng Zhang; Jingcong Ma; Yang Liu; et al. (Global and Planetary Change, 2025)

Promotion mechanism of rare-earth elements doping on performance of CaO/CeO2 sorbent for high temperature CO2 capture - Yunfeng Li; Jiarui Wu; Feng Liu; Weiwei Liu; Bin Li; Qingfa Zhang; Mingfeng Wang; Haiping Yang; Zhen Fang; Zhong Ma (Chemical Engineering Journal, 2025)

Dapagliflozin promotes browning of white adipose tissue through the FGFR1-LKB1-AMPK signaling pathway - Yue Lv; Chengrui Zhao; Qiuyan Jiang; Yilin Rong; Mingfeng Ma; Lili Liang; Weiping Li; Jiuxuan Zhang; Ning Xu; Huiwen Wu (Molecular Biology Reports, 2024)
Background Obesity is associated with a wide variety of metabolic disorders that impose significant burdens on patients and society. The “browning” phenomenon in white adipose tissue (WAT) has emerged as a promising therapeutic strategy to combat metabolic disturbances. However, though the anti-diabetic drug dapagliflozin (DAPA) is thought to promote “browning,” the specific mechanism of this was previously unclear. Methods In this study, C57BL/6 J male mice were used to establish an obesity model by high-fat diet feeding, and 3T3-L1 cells were used to induce mature adipocytes and to explore the role and mechanism of DAPA in “browning” through a combination of in vitro and in vivo experiments. Results The results show that DAPA promotes WAT "browning" and improves metabolic disorders. Furthermore, we discovered that DAPA activated "browning" through the fibroblast growth factor receptors 1-liver kinase B1-adenosine monophosphate-activated protein kinase signaling pathway. Conclusion These findings provide a rational basis for the use of DAPA in treating obesity by promoting the browning of white adipose tissue.

Nitrogen Doping Engineering of V2CTx based Zinc Ion Hybrid Microcapacitors with Quadruple High Energy Density - Wei Lai; Sairao Zhao; Mengdi Guo; Di Wu; Shijun Luo; Chuankun Zhang; Tao Huang; Wenbin He; Mingfeng Li; Xin Zhou; Xiao Luo; Jian Li; et al. (Chemical Engineering Journal, 2024)

Degradation and fermentation of hyaluronic acid by Bacteroides spp. from the human gut microbiota - Ziyi Fang; Mingfeng Ma; Yamin Wang; Wei Dai; Qingsen Shang; Guangli Yu (Carbohydrate Polymers, 2024)

Comparative analysis of the effect of nano‑copper and Cu2O treatment on Cryptocaryon irritans tomonts in large yellow croaker (Larimichthys crocea) farming - Ying Zhou; Quanyin Liu; Kun Hu; Mingfeng Ge; Shengwei Xu; Chengyi Huang; Shan Jin; Rongrong Ma; Jianping Wang (Aquaculture, 2023)

Performance Comparison of Sea Cucumber Detection by the Yolov5 and DETR Approach - Xin Yuan; Shutong Fang; Ning Li; Qiansheng Ma; Ziheng Wang; Mingfeng Gao; Pingpeng Tang; Changli Yu; Yihan Wang; José-Fernán Martínez Ortega (Journal of Marine Science and Engineering, 2023)
Sea cucumber detection represents an important step in underwater environmental perception, which is an indispensable part of the intelligent subsea fishing system. However, water turbidity decreases the clarity of underwater images, presenting a challenge to vision-based underwater target detection. Therefore, accurate, real-time, and lightweight detection models are required. First of all, the development of subsea target detection is summarized in this present work. Object detection methods based on deep learning including YOLOv5 and DETR, which are, respectively, examples of one-stage and anchor-free object detection approaches, have been increasingly applied in underwater detection scenarios. Based on the state-of-the-art underwater sea cucumber detection methods and aiming to provide a reference for practical subsea identification, adjacent and overlapping sea cucumber detection based on YOLOv5 and DETR are investigated and compared in detail. For each approach, the detection experiment is carried out on the derived dataset, which consists of a wide variety of sea cucumber sample images. Experiments demonstrate that YOLOv5 surpasses DETR in low computing consumption and high precision, particularly in the detection of small and dense features. Nevertheless, DETR exhibits rapid development and holds promising prospects in underwater object detection applications, owing to its relatively simple architecture and ingenious attention mechanism.

DNA methylation age acceleration contributes to the development and prediction of non-alcoholic fatty liver disease - Mingfeng Xia; Wenran Li; Huandong Lin; Hailuan Zeng; Shuai Ma; Qi Wu; Hui Ma; Xiaoming Li; Baishen Pan; Jian Gao; Yu Hu; Yun Liu; et al. (GeroScience, 2023)
Non-alcoholic fatty liver disease (NAFLD) is prevalent in the aging society. Despite body weight reduction, the prevalence of NAFLD has been increasing with aging for unknown reasons. Here, we investigate the association of DNA methylation age acceleration, a hallmark of aging, with risk of NAFLD. Genome-wide DNA methylation profiles were measured in 95 participants who developed type 2 diabetes during 4-year follow-up, and 356 randomly sampled participants from Shanghai Changfeng Study. DNA methylation age was calculated using the Horvath’s method, and liver fat content (LFC) was measured using a quantitative ultrasound method. Subjects with highest tertile of DNA methylation age acceleration (≥ 9.5 years) had significantly higher LFC (7.2% vs 3.1%, P = 0.008) but lower body fat percentage (29.7% vs 33.0%, P = 0.032) than those with lowest tertile of DNA methylation age acceleration (< 4.0 years). After adjustment for age, sex, alcohol drinking, cigarette smoking, BMI, waist circumference, and different type blood cell counts, the risk of NAFLD was still significantly increased in the highest tertile group (OR, 4.55; 95% CI, 1.06–19.61). Even in subjects with similar LFC at baseline, DNA methylation age acceleration was associated with higher increase in LFC (4.0 ± 10.7% vs 0.9 ± 9.5%, P = 0.004) after a median of 4-year follow-up. Further analysis found that 6 CpGs of Horvath age predictors were associated with longitudinal changes in LFC after multivariate adjustment and located on genes that might lead to fat redistribution from peripheral adipose to liver. Combination of the key CpG methylation related to liver fat content with conventional risk factors improves the performance for NAFLD prediction. Graphical Abstract

A novel approach to achieving more efficient production of the mature form of human IL-37 in plants - Yao Zhang; Nadiyah Alqazlan; Zihe Meng; Jingyao Zhao; Nan Liu; Yuxin Zhang; Mingfeng Feng; Shengwu Ma; Aoxue Wang (Transgenic Research, 2023)

Machine Learning-Based Prediction of Dynamic Responses of a Tower Crane under Strong Coastal Winds - Qiang Li; Weijie Fan; Mingfeng Huang; Heng Jin; Jun Zhang; Jiaxing Ma (Journal of Marine Science and Engineering, 2023)
With the rapid development of the construction industry, tower cranes are increasingly used in coastal engineering. However, due to the complexity of their operating environment, tower cranes are vulnerable to typhoons, thunderstorms, and other extreme natural disasters. Therefore, it is becoming increasingly important to carry out safety warnings for the tower crane structure under the action of strong winds. In this paper, a real-time monitoring system for tower responses based on the Internet of things (IoT), which realizes long-term monitoring of the whole process of tower crane operation, was built. Based on the long-term monitoring data and the machine learning algorithm, two tower response prediction models were established. During the transit of super typhoon In-fa, the maximum displacement of the tower structure was predicted in advance, based on the measured wind speed data at the site, which is in good agreement with the displacement data monitored by the IoT. The results show that under strong winds, the non-working tower has a response lag, resulting in the fact that its maximum displacement does not correspond to the maximum wind speed moment at the site. This is mainly due to the weathercock effect of the tower in the non-working condition. The prediction model proposed in this paper can provide timely and effective safety warnings for the tower structure. It also can provide useful engineering references and scientific structural safety warning suggestions for the same type of tower cranes that do not have IoT monitoring systems installed.

Overexpressing 4-coumaroyl-CoA ligase and stilbene synthase fusion genes in red raspberry plants leads to resveratrol accumulation and improved resistance against Botrytis cinerea - Junxin Zhang; Xihuan Yan; Tiran Huang; Huan Liu; Fang Liu; Meixia Yang; MingFeng Yang; Lanqing Ma (Journal of Plant Biochemistry and Biotechnology, 2023)

The genesis of the Ni–Cu sulfide mineralization of the carboniferous Haibaotan intrusion, Eastern Tianshan, Central Asian Orogenic Belt - Mingfeng Qiu; Yun Zhao; Chunji Xue; Jia Chen; Xiaoping Ma; Lu Wang; Liang Yu; Yanxiang You (International Journal of Earth Sciences, 2023)

Overexpressing codon-adapted fusion proteins of 4-coumaroyl-CoA ligase (4CL) and stilbene synthase (STS) for resveratrol production in Chlamydomonas reinhardtii - Chen Xiang; Jia Liu; Lanqing Ma; MingFeng Yang (Journal of Applied Phycology, 2020)

Overexpressing fusion proteins of 4-coumaroyl-CoA ligase (4CL) and stilbene synthase (STS) in tobacco plants leading to resveratrol accumulation and improved stress tolerance - Xuancheng He; Feiyan Xue; Lulu Zhang; Huili Guo; Lanqing Ma; Mingfeng Yang (Plant Biotechnology Reports, 2018)

Lipid desaturation in prokaryotic pathway abates the high-oleic phenotype of FAD2-silenced tobacco at lower temperature - Lulu Zhang; Heshu Lu; Chunmei Liu; Feiyan Xue; Jing Yang; Lanqing Ma; Mingfeng Yang (Journal of Plant Biochemistry and Biotechnology, 2016)

Scaffold-based design of xanthine as highly potent inhibitors of DPP-IV for improving glucose homeostasis in DIO mice - Yan Ran; Heying Pei; Caifeng Xie; Liang Ma; Yuzhe Wu; Kai Lei; Mingfeng Shao; Minghai Tang; Mingli Xiang; Aihua Peng; Yuquan Wei; Lijuan Chen (Molecular Diversity, 2015)

Advanced glycation end products promote proliferation and suppress autophagy via reduction of Cathepsin D in rat vascular smooth muscle cells - Mingfeng Ma; Xiaofan Guo; Ye Chang; Chao Li; Xin Meng; Si Li; Zhen-Xian Du; Hua-Qin Wang; Yingxian Sun (Molecular and Cellular Biochemistry, 2015)

A high-density intervarietal map of the wheat genome enriched with markers derived from expressed sequence tags - Shulin Xue; Zhengzhi Zhang; Feng Lin; Zhongxin Kong; Yong Cao; Chunjun Li; Hongying Yi; Mingfeng Mei; Huilan Zhu; Jizhong Wu; Haibin Xu; Dongmei Zhao; et al. (Theoretical and Applied Genetics, 2008)